Державні перевороти, революції й політична боротьба у світлі компаративістики (на основі аналізу візії В.Леніна та сучасних концептуалізацій) - Кучерук, М. (Український історичний журнал, 2022)
Мета дослідження – провести паралелі між методологічними працями В.Леніна
і практикою більшовиків та сучасними візіями «гібридної війни». Методологія. Використано
такі методи: герменевтичний, компаративний, ретроспективний. Окреслення компаративних
паралелей у студіях В.Леніна й сучасних теоретиків «гібридної війни» (передусім російських)
дозволяє зробити припущення щодо існування певної традиції в політиці суміжної держави
щодо України. Наукова новизна полягає у спробі переосмислення інтелектуальної спадщини
В.Леніна, зокрема його поглядів на революційну війну, і визначення їх впливу на розвиток
сучасних концепцій «гібридних воєн». Основні результати дослідження. Робиться спроба
переоцінити особистість В.Леніна й поглянути на його внесок в історію не стільки як політичного
діяча, що створив нову державу, а як на методолога та розробника стратегії взяття влади,
котра містила у собі елементи теорії, доопрацьованої і трансформованої сучасними фахівцями,
і відомої нині як «гібридна війна». Сам В.Ленін зауважував, чим війна проти «капіталу» відрізняється
від традиційної: вона може бути безкровною, також це війна педагогічна, економічна
тощо. Такий тип війни ми спостерігаємо в наші дні. Вождь російських більшовиків указував на
три складові успіху своєї партії: ідеологія, організація, пропаґанда й аґітація. Аналіз сучасних
подій дає підстави вважати, що «гібридна війна» в першу чергу спрямована на захоплення
мізків людей, а вже потім – на завоювання територій. У В.Леніна ми знаходимо твердження
про надзвичайну роль ідеології. Для більшовиків простого завоювання мало, вони йдуть
далі – переконати противника у своїй правоті та в його (противника) неспроможності. Цьому
допомагали пропаґанда й аґітація. А жорстка армійська дисципліна та вимога від партійних
кадрів бути справжніми професіоналами сприяли реалізації планів. The purpose of the research. The author makes an attempt to draw parallels between
the methodological works of V.Lenin and the practice of the Bolsheviks and modern visions of
Hybrid Warfare. The novelty of the study lies in the endeavor to rethink V.Lenin’s intellectual
heritage, in particular his views on the revolutionary war, and to determine their impact on the
development of modern concepts of hybrid wars. The research methodology. The following
general historical methods have been used: hermeneutic, historical-comparative, and retrospective.
Outlining comparative parallels in the works of V.Lenin and modern theorists of Hybrid Warfare
(especially Russian) allows us to make assumptions about the existence of a certain tradition in the
policy of the neighboring country towards Ukraine. The issue. This article is an attempt to reevaluate
V.Lenin’s personality and look at his contribution to history not so much as a politician
who created a new state, but as a methodologist and developer of the strategy of seizure of power,
which contained elements of theory refined and transformed by modern experts. now known as
the Hybrid War. V.Lenin itself realized that his theory was pointed toward the goal of gaining
and holding power, and operated the terms “dialectics”, and “war against capital” in contrast to
“traditional war” and made a clear difference between traditional and non-traditional war. He
considered that non-traditional war could bloodless, likewise educational, economical, “violent
and peaceful, military and economic”. In other words, that type of war we can see currently,
though was somehow changed accordingly to the capacities of modern devices and the lifestyles of
our contemporaries. V.Lenin points out the constituents of his m ethodology. These are ideology,
organization, propaganda, and agitation. Recent events demonstrate to us that initially Hybrid
War is determined to capture the human mind, and reaping the territories and countries come
after that. Absolutely definitely we see the exceptional role in V.Lenin’s m ethodology. That’s
why V.Lenin never starts the debates without referring to the ideological questions. Ideology is
always the thing from which he starts. But subjugation is not enough for the Bolsheviks, they go
far – to persuade their adversaries of the wrongness. Propaganda and agitation helped V.Lenin to
disseminate his influence over the population. And a strict, really military discipline in the party,
the high level of the professional demands to the members of the Bolshevik organization, and the
condition to be the expert in revolution helped to realize the plans.